2018
DOI: 10.3126/njenthns.v6i1.19437
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Facial and Head and Neck Trauma at Patan Hospital

Abstract: Objective: To find out the prevalence of various types of head and neck trauma.Material and Methods: This retrospective study was done in the department of ENT and HNS, Patan Hospital, PAHS. Charts were retrospectively reviewed for total 61 inpatients with a diagnosis suggestive of head and neck trauma from August 2013 to January 2015. Data was collected for  age, sex, address, type of admission (emergency/OPD), mechanism of injury, site of injury , imaging including X-rays/CT scan wherever applicable and resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The sample showed an increasing male-tofemale ratio with age, consistent with previous studies, from 1.1:1 in children under 10 years old to 1.6:1 in children over 10 years old [1,2]. A study has suggested that smaller discrepancy in preschool children could be attributed to age-related activities, typical of childhood [2]. The higher rate of incidences pertaining to facial injuries in older children and adolescents among males may be attributed to their greater involvement in outdoor activities, sports, and violence.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The sample showed an increasing male-tofemale ratio with age, consistent with previous studies, from 1.1:1 in children under 10 years old to 1.6:1 in children over 10 years old [1,2]. A study has suggested that smaller discrepancy in preschool children could be attributed to age-related activities, typical of childhood [2]. The higher rate of incidences pertaining to facial injuries in older children and adolescents among males may be attributed to their greater involvement in outdoor activities, sports, and violence.…”
Section: Resultssupporting
confidence: 90%
“…Several earlier investigations have reported a male predominance in facial trauma, with sex ratios ranging from 1.6:1 to 3.3:1 [16][17][18][19]. The sample showed an increasing male-tofemale ratio with age, consistent with previous studies, from 1.1:1 in children under 10 years old to 1.6:1 in children over 10 years old [1,2]. A study has suggested that smaller discrepancy in preschool children could be attributed to age-related activities, typical of childhood [2].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations